2016
DOI: 10.1523/jneurosci.0046-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Plasticity in Higher-Order Auditory Cortex of Congenitally Deaf Cats Does Not Limit Auditory Responsiveness to Cochlear Implants

Abstract: Congenital sensory deprivation can lead to reorganization of the deprived cortical regions by another sensory system. Such cross-modal reorganization may either compete with or complement the "original" inputs to the deprived area after sensory restoration and can thus be either adverse or beneficial for sensory restoration. In congenital deafness, a previous inactivation study documented that supranormal visual behavior was mediated by higher-order auditory fields in congenitally deaf cats (CDCs). However, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 72 publications
12
68
2
1
Order By: Relevance
“…However, the findings of this study do not support this hypothesis: longitudinal optical imaging of the human brain presented here reveals that increased cross-modal activation of auditory brain regions by lip-reading neither precludes an increase in cortical responsiveness to auditory speech, nor limits the recovery of speech understanding after implantation. Our findings in cochlear implanted adults parallel recent findings in an animal model showing that cross-modal plasticity within auditory brain regions does not preclude responsiveness to auditory stimulation with a CI and therefore should not be considered strictly maladaptive as traditionally thought (19). On the contrary, here we show that increased cross-modal activation after adult cochlear implantation is associated with increased auditory responsiveness and better speech understanding with a CI, indicating an adaptive benefit of crossmodal plasticity following implantation.…”
Section: Discussionsupporting
confidence: 88%
“…However, the findings of this study do not support this hypothesis: longitudinal optical imaging of the human brain presented here reveals that increased cross-modal activation of auditory brain regions by lip-reading neither precludes an increase in cortical responsiveness to auditory speech, nor limits the recovery of speech understanding after implantation. Our findings in cochlear implanted adults parallel recent findings in an animal model showing that cross-modal plasticity within auditory brain regions does not preclude responsiveness to auditory stimulation with a CI and therefore should not be considered strictly maladaptive as traditionally thought (19). On the contrary, here we show that increased cross-modal activation after adult cochlear implantation is associated with increased auditory responsiveness and better speech understanding with a CI, indicating an adaptive benefit of crossmodal plasticity following implantation.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, in previous studies, field specificity in the capacity for cross‐modal takeover following congenital deafness has been documented: visual cross‐modal function was demonstrated in secondary fields DZ and PAF in CDCs (Lomber, Meredith, & Kral, ; Land et al, ), but not in primary fields A1 and anterior auditory field (AAF; Kral, Schroder, Klinke, & Engel, ; Lomber et al, ). AAF, however, showed somatosensory recruitment in cats deafened within the first month of life (Meredith & Lomber, ).…”
Section: Introductionmentioning
confidence: 91%
“…It remains unclear whether deficits as described in field A1 also involve higher‐order fields. While it has been shown that auditory responsiveness is preserved in field DZ of CDCs along with increased visual responsiveness (Land et al, ), the only previous direct comparison between two cortical hierarchical levels (primary vs. secondary) relates to connection patterns (Barone et al, ). Furthermore, cortical minicolumns, the smallest functional unit in the cerebral cortex (Mountcastle, ), have been investigated functionally and deficits in columnar activation patterns were described in field A1 of CDCs (Kral, Hartmann, Tillein, Heid, & Klinke, ; Kral, Tillein, Heid, Hartmann, & Klinke, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these studies indicate both structural and functional reorganization in deaf cats, and auditory regions that are recruited for specific visual functions. The relationship between these reorganized auditory areas and later auditory habilitation via a cochlear implant was further investigated in translational work, which showed that auditory areas responsive to visual cues still retain their responsiveness to native auditory inputs although they appear to lack bimodal interactions (Land et al 2016). This, like other findings in humans, suggests that auditory processing can be successfully engaged while multisensory integrative abilities are altered or absent.…”
Section: Cross Modal Plasticity/animal Modelsmentioning
confidence: 99%